PERANAN GURU DALAM PENGEMBANGAN KECERDASAN INTERPERSONAL ANAK 5-6 TAHUN DI TK MUJAHIDIN 1 - Wahyuni, Kanti; Fadillah, Fadillah; R, Marmawi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
describe the role of teacher’s in developing interpersonal intelligence of aged 5-6 years at the Mujahidin 1 Kindergarten South Pontianak. The method use isn this research is descriptive method with a quantitative research approach. Data subjects in this research are 12 teacher’s grup B who have a role in the development of children’s interpersonal intelligence, especially in ascapts of motivator, mediator, facilitator, and evaluator. The techniques used in this research were used of questionnaires and documentation using data collection tools like is a questinneaire, and documentation picture. The results of data analysis show that the role of teacher’s in developing interpersonal intelligence of aged 5-6 years in in classified as moderate, it can be see from the results of presentations that show that more than 50% of teacher’s have a good roles properly, especially in ascapts of motivator, mediator, facilitator, and evaluator.Keyword : Interpersonal, Motivator, The Role of Teacher’s